THE 22-YEAR PROSPECTIVE QUEBEC (PROQ) STUDY ON WORK AND HEALTH CONDUCTED AMONG 9000 WHITE-COLLAR WORKERS. (June 2018) - Trudel, X.; Gilbert-Ouimet, M.; Milot, A.; Duchaine, C.; Vézina, M.; Laurin, D.; Sultan-Taïeb, H.; Brisson, C.
Abstract : Objective: Cardiovascular diseases (CVD) are the leading cause of mortality worldwide accounting for 17.7 million deaths per year. Mental health problems (MHP) are the first cause of disability worldwide. Their prevalence, long duration and high risk of recurrence place a considerable burden on health and social care systems and important productivity losses for employers. The PROspective Quebec (PROQ) Study on Work and Health is a prospective cohort initiated in 1991-93 to further extend our comprehension of the effect of work stressors on cardiovascular and mental health outcomes. Design and method: At baseline (1991–1993), the study population involved 9, 189 white-collar workers aged 18 to 65 years-old employed by 19 specific public organizations in Quebec City. At the first follow-up, 8 years later (1999–2001), 8, 121 workers agreed to participate again corresponding to 89% of the initial sample. The 22-year follow-up (2015–18) is currently ongoing. This second follow-up includes measurements at later life of a large number of cardiovascular and mental health outcomes as well as their major risk factors, including blood pressure. Results: Data collection procedures are a self-reported questionnaire, an interview, biological variables and medico-administrative databases extractions. This prospective cohort will fill important research gaps related to: 1) the pathways by which adverse psychosocial work stressors cumulated over the working life could lead to higher risk of cardiovascular diseases (CVD) and mental health problems (MHP) at older ages, 2) the effects of psychosocial work stressors on novel subclinical markers of disease risk (aortic stiffness, inflammatory markers, telomere length, cognitive function) and 3) the costs of CVD and mental health problems attributable to work stressors. Conclusions: This cohort is one of the most rigorous and extensive occupational cohorts in the world. The results will contribute substantially to the primary prevention of CVD and MHP.